An introduction to health planning in developing countries - Green, Andrew, 1952-; Oxford University Press (Oxford [England] ; New York : Oxford University Press, 1999)
This is the second edition of the text aimed at planners and health policy makers involved in planning for health in developing countries. It explains the importance of health planning, outlines the policy context internationally and then looks at each stage in the Planning Spiral
Foreword Anne Mills Preface A. Green What is planning, and why plan? Approaches to planning The policy context: Primary health care and health sector reform Planning for health Financing health care Information for planning Situational analysis Setting priorities Costs and costing Optional appraisal and evaluation Resource allocation and budgeting Programmes, projects, implementation, and monitoring Planning human resources The state of planning and planning for the State.
Includes bibliographical references and index.
Keywords: Health planning -- Developing countries; National health services -- Developing countries